Sakinah Family Empowerment by Optimizing the Role of BP4 and Parents Mental Revolution Perspective - Hariyanto, Erie; Hannan, Abd; Wahyudi, Arif; Susylawati, Eka; Tri Wahyu Faizal, Bhismoadi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This study examines a sakinah family empowerment by optimizing the role of Badan Penasihat Pembinaan dan Pelestarian Perkawinan (Body for Marital Advisory Guidance and Maintenance (BMAGM)) and parents from a mental revolution perspective. There are three research questions: What is the so-called BMAGM? What and how is the correlation between the national revolution movement and sakinah family empowerment in Indonesia? What strategies are carried out in doing mental revolution in a family in order to have a sakinah family? This qualitative research collected both primary and secondary data. Three essential findings in this study are as follows. First, BMAGM is a legal social-religious organization whose particular duty is to cope with problems in a family. Second, there are three programs in the National Mental Revolution Movement (NMRM) as stated in the Presidential Instruction No. 12 of 2016 i.e. Indonesia in Order Movement (IOM) in point H/8; United Indonesia Movement (UIM) point J/10; Clean Indonesia Movement (CIM) point A/1. Third, in the perspective of the National Mental Revolution Movement (NMRM), parents’ role is essential. Therefore, parents are a strategic issue and should be prioritized in building sakinah family in Indonesia.